ROLE OF NO-SYNTHASE ISOFORMS IN THE MECHANISMS OF DISORDERS RELATED TO FREE-RADICAL PROCESSES IN SALIVARY GLAND UNDER COMBINE EXCESSIVE INTAKE OF SODIUM NITRATE AND FLUORIDE - Стасюк, О.А. (World of Medicine and Biology, 2012)
The role of NO-synthase isoforms in the mechanisms of disorders related to oxidative processes in the submandibular salivary gland tissue (SG) under sodium nitrate and fluoride combined excessive intake has been studied in the experiment on 50 white rats. We have found the introduction of a selective inhibitor of inducible NO-synthase (iNOS) aminoguanidine under chronic intoxication with sodium nitrate and fluoride decreases superoxide anion radical ) production by microsomal and mitochondrial electron transport chains (ETC) in the SG tissues, limits lipid peroxidation and increases antioxidant potential, antioxidant enzymes (superoxide dismutase and catalase) activity, that it indicates the role of endogenous NO, produced with the participation of iNOS, in free radical processes activation and antioxidant defense inhibition in SG. The introduction of a selective inhibitor of neuronal NOS (nNOS) 7-nitroindazole and substrate NOS L-arginine, on the contrary, increases . production by mitochondrial ETC, and reduces antioxidant potential.